The VCG Auction in Theory and Practice - Varian, Hal R.; Harris, Christopher (American Economic Review, 2014)
We describe two auction forms for search engine advertising and present two simple theoretical results concerning i) the estimation of click-through rates and ii) how to adjust the auctions for broad match search. We also describe some of the practical issues involved in implementing a VCG auction.